Design of E.R. Building At Ct Arsa Palu Hospital With Liquefaction Potential - Ghozi, Mohammad; Yulianto, Achmad; Budiati, Anik (Dinasti Research, 2024)
This design hospital building is planned to be built in the city of Palu. Palu City has high earthquake potential, has history of liquefaction, tsunami and landslides disasters. Thorough design is needed so that this hospital building still become a place for health services after a disaster occurs. The building was designed using the Special Moment Resisting Frame Structure system based on the SNI. Earthquake load analysis uses the response spectrum method based on Earthquake Resistance Planning Procedures (SNI 1726:2019). This concept obtains structure design that meets SNI and still strong in strong earthquake and liquefaction. Analysis has been carried out and it was found that the potential for liquefaction to occur at a depth of 1.5 M to 4.5 M so that the foundation chosen was 4 piles with a diameter of 40 cm, a depth of 6 meters per pile cap. From the results of calculations, it shows that the structure of the emergency room building at CT Arsa Palu Hospital is safe from an analytical perspective.